The Ethical Leadership Project. It’s role as a key contributor for a morally transformed society - Dames, GE (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
The objective of this article is to introduce the work of the Ethical Leadership Project to the broader scientific public; and to document the project’s specific contribution. This is the first in a series of articles which focus on the various research activities of the project. The project’s central contribution is in the development of ethical leadership on all levels of society, for example, religious and secular traditions, family, youth, gender, labour, business, politics, education, media, sports, arts and culture. New Modes for moral transformation were explored to foster ethical leadership knowledge, values and skills. The vision of ethical leadership has been developed through evidence-based and participatory research; education, training and skills development through different conference and workshop proceedings. The ELP embodies in essence the development of a “RDP of the soul” conviction fostering ethical leadership for a morally transformed society.